Stability Analysis of Distributed Order Fractional Differential Equations - H. Saberi Najafi; A. Refahi Sheikhani; A. Ansari (Abstract and Applied Analysis)
We analyze the stability of three classes of distributed order fractional differential equations (DOFDEs) with respect to the nonnegative density function. In this sense, we discover a robust stability condition for these systems based on characteristic function and new inertia concept of a matrix with respect to the density function. Moreover, we check the stability of a distributed order fractional WINDMI system to illustrate the validity of proposed procedure.